2016
DOI: 10.1159/000453184
|View full text |Cite
|
Sign up to set email alerts
|

Elevated THBS2, COL1A2, and SPP1 Expression Levels as Predictors of Gastric Cancer Prognosis

Abstract: Background/Aims:Gastric cancer (GC) is an important health problem. Classification based on molecular subtypes may help to determine the prognosis of patients with GC. Tumor invasion and metastasis are important factors affecting the prognosis of cancer. We aimed to identify genes related to tumor invasion and metastasis, which may serve as indicators of good GC prognosis. Methods:Tumor tissues and adjacent normal tissues were collected from 105 patients with primary GC who were treated by undergoing radical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
61
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 28 publications
5
61
0
3
Order By: Relevance
“…We found that COL1A2, COL6A3, and THBS2 genes were mainly involved in ECM‐receptor interaction and PI3K‐Akt signaling pathway through KEGG pathway‐enrichment analysis. THBS2 was found to express highly in gastric cancer tissues, besides, THBS2, and COL1A2 play a critical role in the ECM‐receptor interaction pathway . It is also reported that focal adhesion pathway (THBS2, PDGFD, MAPK1, COL1A2, and COL6A3), ECM‐receptor interaction pathway (THBS2, COL1A2, COL6A3, and FN1) and TGF‐beta signaling (THBS2, MAPK1, and INHBA) were the key differences in tumor growth and normal expression of gastric cancer at a molecular level .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…We found that COL1A2, COL6A3, and THBS2 genes were mainly involved in ECM‐receptor interaction and PI3K‐Akt signaling pathway through KEGG pathway‐enrichment analysis. THBS2 was found to express highly in gastric cancer tissues, besides, THBS2, and COL1A2 play a critical role in the ECM‐receptor interaction pathway . It is also reported that focal adhesion pathway (THBS2, PDGFD, MAPK1, COL1A2, and COL6A3), ECM‐receptor interaction pathway (THBS2, COL1A2, COL6A3, and FN1) and TGF‐beta signaling (THBS2, MAPK1, and INHBA) were the key differences in tumor growth and normal expression of gastric cancer at a molecular level .…”
Section: Discussionmentioning
confidence: 96%
“…THBS2 was found to express highly in gastric cancer tissues, besides, THBS2, and COL1A2 play a critical role in the ECM-receptor interaction pathway. 15 It is also reported that focal adhesion pathway (THBS2, PDGFD, MAPK1, COL1A2, and COL6A3), ECM-receptor interaction after the scratch was drawn (×150); B, BGC-823 cell migration ability in each group. C, SGC-7901 cell migration at the same region 0 h and 24 h after the scratch was drawn (×150); D, SGC-7901 cell migration ability in each group; *, P < 0.05 when compared with the blank group and the NC group; NC, negative control pathway (THBS2, COL1A2, COL6A3, and FN1) and TGFbeta signaling (THBS2, MAPK1, and INHBA) were the key differences in tumor growth and normal expression of gastric cancer at a molecular level.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Expression levels of FGFR2 and TSPs assessed independently have been reported in several studies as prognostic factors for patients with GC [17][18][19][20]. As a follow-on from our previous study, which demonstrated that FGFR2 promotes GC cells invasion and migration by targeting TSPs in vitro [16], we undertook an evaluation of the potential clinical significance and mechanism of the relationship between FGFR2 and TSP4 in GC.…”
Section: Discussionmentioning
confidence: 93%
“…As numerous genetic changes are in relation to cancer cell invasion and metastasis,14, 19, 20, 21, 22 great efforts have been made in the identification of novel key regulators and the potential mechanisms involved in this process over the years. Interestingly, recent studies have revealed that CRYAB is aberrantly overexpressed in various types of cancer, and its expression could promote cell invasion and metastasis 8, 9, 10.…”
Section: Discussionmentioning
confidence: 99%